2020
DOI: 10.1038/s41598-019-57245-6
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal vaccination with Listeria ivanovii as vector of Mycobacterium tuberculosis antigens promotes specific lung-localized cellular and humoral immune responses

Abstract: We have previously demonstrated that a recombinant Listeria ivanovii (LI) strain expressing the ESAT-6 or Ag85C protein of Mycobacterium tuberculosis (Mtb) as a tuberculosis (TB) vaccine candidates induced antigen-specific cellular immune responses after intravenous immunization of mice. However, whether such recombinant strains could induce desired immune responses in the lung, where TB infection occurs, is not clear. In this paper, C57BL/6 J mice were intranasally vaccinated with attenuated LIΔactAplcB-Rv387… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Several studies reported that repeated immunization with the same attenuated LM-based TB vaccine candidate could induce potent antigen-specific T cell responses by intraperitoneal ( 14 ), intracutaneous ( 12 ) vaccination as well as intravenous ( 13 ) inoculation. Similar to these results, Jiang et al ( 15 ) found that mice vaccinated intranasally with the same LI-vectored TB vaccine candidate induced promising lung-localized cellular and humoral immune responses. As shown in Figure 4 , our results also confirmed that repeated immunization with the same strain was more effective than single-dose immunization.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Several studies reported that repeated immunization with the same attenuated LM-based TB vaccine candidate could induce potent antigen-specific T cell responses by intraperitoneal ( 14 ), intracutaneous ( 12 ) vaccination as well as intravenous ( 13 ) inoculation. Similar to these results, Jiang et al ( 15 ) found that mice vaccinated intranasally with the same LI-vectored TB vaccine candidate induced promising lung-localized cellular and humoral immune responses. As shown in Figure 4 , our results also confirmed that repeated immunization with the same strain was more effective than single-dose immunization.…”
Section: Discussionsupporting
confidence: 60%
“…Attenuated LM has been developed as a vaccine vector for TB vaccine candidates ( 11 14 ). Recently, we constructed two attenuated LI recombinant strains expressing Ag85A or ESAT-6, which induced potent CD4 + and CD8 + T cell responses either in the spleen after intravenous immunization ( 10 ) or in the lung after intranasal vaccination ( 15 ). Therefore, the facultative intracellular Listeria strain is considered as a promising delivery system since it induces strong CD4 + and CD8 + cell-mediated immune response ( 9 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative to viral vector vaccines, attenuated bacterial vector vaccines are also being considered. An intriguing bacterial vector for TB vaccine development is attenuated Listeria [105,111]. Listeria-vectored vaccines are well established to be safe in immunocompetent humans, inexpensive to produce, present antigens to both MHC-I and MHC-II, and importantly, prior immunity to the vector also does not affect its efficacy unlike viral vectors [105].…”
Section: Bacterial Vector Vaccinesmentioning
confidence: 99%
“…The nine genes contained in this module are all involved in the biosynthetic process for arabinose. For example, the Rv0129c coding protein plays a role in the addition of mycosyl residues in the cell wall arabinose (Jiang et al, 2020) and Rv3806c plays a role in the synthesis of decenyl phosphate D-arabinose (Safi et al, 2013).…”
Section: Analysis Of the M Tuberculosis Cell Wall-related Modulesmentioning
confidence: 99%